Characterization of the Fungitoxic Activity on Botrytis cinerea of N-phenyl-driman-9-carboxamides - Ricardo Melo; Verónica Armstrong; Freddy Navarro; Paulo Castro; Leonora Mendoza; Milena Cotoras (Journal of Fungi, 2021)
A total of 12 compounds were synthesized from the natural sesquiterpene (-) drimenol (compounds 4 to 15). The synthesized compounds corresponded to N-phenyl-driman-9-carboxamide derivatives, similar to some fungicides that inhibit the electron-transport chain. Their structures were characterized and confirmed by 1H NMR, 13C NMR spectroscopy, and mass spectrometry. Compounds 5 to 15 corresponded to novel compounds. The effect of the compounds on the mycelial growth of Botrytis cinerea was evaluated. Methoxylated and chlorinated compounds in the aromatic ring (compounds 6, 7, 12, and 13) exhibited the highest antifungal activity with IC50 values between 0.20 and 0.26 mM. On the other hand, the effect on conidial germination of B. cinerea of one methoxylated compound (6) and one chlorinated compound (7) was analyzed, and no inhibition was observed. Additionally, compound 7 decreased 36% the rate of oxygen consumption by germinating conidia.